2019
DOI: 10.3791/59313
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Live-cell Flow Cytometry to Investigate Calcium Influx, Pore Formation, and Phagocytosis by P2X7 Receptors in Adult Neural Progenitor Cells

Abstract: Live-cell flow cytometry is increasingly used among cell biologists to quantify biological processes in a living cell culture. This protocol describes a method whereby live-cell flow cytometry is extended upon to analyze the multiple functions of P2X7 receptor activation in real-time. Using a time module installed on a flow cytometer, live-cell functionality can be assessed and plotted over a given time period to explore the kinetics of calcium influx, transmembrane pore formation, and phagocytosis. This simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…To determine whether EX7_EX8del protein isoforms form functional receptors, patch‐clamping and Ca + flux was used to measure channel function, and ethidium + uptake measured by time resolved flow cytometry was used to analyze pore function in HEK 293 cells transiently transfected with either P2X7A, P2X7L, or P2X7E. In addition, phagocytic function, in the absence of ATP, was analyzed by measuring the uptake of YG beads using flow cytometry . Channel and pore function were not detected in either P2X7E or P2X7L transfected cells (Figure A–C), however P2X7L showed the same level of phagocytic function compared to P2X7A (Figure D).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…To determine whether EX7_EX8del protein isoforms form functional receptors, patch‐clamping and Ca + flux was used to measure channel function, and ethidium + uptake measured by time resolved flow cytometry was used to analyze pore function in HEK 293 cells transiently transfected with either P2X7A, P2X7L, or P2X7E. In addition, phagocytic function, in the absence of ATP, was analyzed by measuring the uptake of YG beads using flow cytometry . Channel and pore function were not detected in either P2X7E or P2X7L transfected cells (Figure A–C), however P2X7L showed the same level of phagocytic function compared to P2X7A (Figure D).…”
Section: Resultsmentioning
confidence: 87%
“…In addition, phagocytic function, in the absence of ATP, was analyzed by measuring the uptake of YG beads using flow cytometry. 8,9,39 Channel and pore function were not detected in either P2X7E or P2X7L transfected cells ( Figure 7A-C), however P2X7L showed the same level of phagocytic function compared to P2X7A ( Figure 7D). P2X7E, which is not trafficked to the cell surface, failed to confer phagocytic function ( Figure 7D).…”
Section: P2x7l Has Phagocytic But Not Channel or Pore Functionmentioning
confidence: 96%
“…This work is a continuation of the study of the anti-inflammatory activity of the acyclic thioglucoside U-548 and its tetracyclic derivative U-286. In earlier research these compounds were found to exhibit antagonistic properties associated with blocking reaction pathways mediated by P 2 X 7 R in macrophage and neuronal cells in vitro [21,22]. Activation of P 2 X 7 R induces large-scale release of ATP into the extracellular space of tissues, due to its ability to form membrane macropores, as well as activate pannexin-1 hemichannels, thereby enhancing purinergic signaling and the inflammatory process [24].…”
Section: Discussionmentioning
confidence: 99%
“…Studied compounds U-286 [(2R,3R,4S,4aR,12aS)-2-hydroxymethyl-3,4-dihydroxy-3,4,4a,12a-tetrahydro-2H-naphtho(2, 3-b) pyrano(2,3-e)(1,4)-oxathiine-6, 11-dione] and U-548 [3-(β-D-glucopyranosyl-1-thio)-2methoxynaphthalene-1,4-dione] were synthesized in accordance with early described protocols [22]. Stocks of compounds were prepared in dimethyl sulfoxide (DMSO, Biolot, Russia) as 10 mmol/L solutions.…”
Section: Synthesis Of 14-nqs and Solution Preparationmentioning
confidence: 99%
See 1 more Smart Citation